Konsep Teologi Ekologis dalam Ritual Ngeti Uma pada Masyarakat Ende-Lio - Alfredo Reynold Reba; Sefrianus Juhani; Aprilius Bedu Beke; Bruno Rhaki Mbani; Edwinandus Dhajo Reda; Fransiskus B. Bop Dala; Karolus Dule (Jurnal Penelitian Pendidikan Agama Katolik, 2022)
The environmental crisis is one of the problems which is always related to human life. Meanwhile, there are various cultural traditions that teach love, respect, and harmony with nature and the environment. Morever, these traditions often convey the Creator as the provider and the giver of the harmony. They believe that the environmental crises might have been caused by the fading understanding of God as the creator and preserver of the universe. This belief in fact is the principle of Ngeti Uma ritual. This paper aims to find the true concept of God and His relationship with creations in the Ngeti Uma Ritual of the Ende-Lio community. The research for this paper uses a qualitative approach with ethnographic methods. Data were obtained through interviews with key informants. The research find out in the ritual there is indeed a concept of belief in God and His relationship with the creations. God is called Du'a Nngga'e. This concept has its similarities with the teaching of the Catholic Church. God is seen as the creator, organizer, as well as the giver of the fertility of soil and the growth of nature.